2013
DOI: 10.1021/am400220s
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Cationic Conjugated Polyelectrolytes and Oligomers against Saccharomyces cerevisiae Vegetative Cells and Ascospores

Abstract: The antifungal activities of poly(phenylene ethynylene) (PPE)-based cationic conjugated polyelectrolytes (CPEs) and oligo-phenylene ethynylenes (OPEs) were investigated using Saccharomyces cerevisiae (S. cerevisiae) as a model pathogen. The effect of the CPE and OPE materials on the vegetative cells and ascospores were tested in the dark or with UV-irradiation. A number of the tested polymers and oligomers significantly reduced the viability of the vegetative yeast cells in the dark, with activities exceeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
(71 reference statements)
2
32
0
Order By: Relevance
“…C. glabrata is noted for its resistance to killing by cationic antimicrobial peptides in comparison to C. albicans and other pathogenic Candida species (54)(55)(56). Furthermore, the decreased ability of EO-OPE-DABCO to kill C. glabrata resembles the results of a previous study, in which a 10-g/ml concentration of the compound failed to kill 99% of S. cerevisiae yeast cells, even after an hour in the light (23). Although S. cerevisiae is benign, it is closely related to C. glabrata (32,36).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…C. glabrata is noted for its resistance to killing by cationic antimicrobial peptides in comparison to C. albicans and other pathogenic Candida species (54)(55)(56). Furthermore, the decreased ability of EO-OPE-DABCO to kill C. glabrata resembles the results of a previous study, in which a 10-g/ml concentration of the compound failed to kill 99% of S. cerevisiae yeast cells, even after an hour in the light (23). Although S. cerevisiae is benign, it is closely related to C. glabrata (32,36).…”
Section: Discussionsupporting
confidence: 65%
“…A subset of conjugated polyelectrolytes, phenylene ethynylenes, have shown promising biocidal activity against Gram-positive and -negative bacterial pathogens, as well as the environmental yeast Saccharomyces cerevisiae (21)(22)(23). The chemical structure of these compounds renders them capable of inducing broad-spectrum cell damage.…”
mentioning
confidence: 99%
“…Many types of antimicrobial polymers based on poly(phenylene ethynylene) cationic conjugated polyelectrolytes were investigated by Whitten and co-workers [85]. In a recent study, antifungal activity of poly(phenylene ethynylene) polyelectrolytes (Table 2F) and oligo-phenylene ethynylenes were investigated [81]. The polycations effectively inhibited the fungus Saccharomyces cerevisiae, an opportunistic human pathogen, both in the dark and under ultraviolet (UV)/visible light irradiation.…”
Section: Amphiphilic Homopolymersmentioning
confidence: 99%
“…They investigated telechelic antimicrobial function of poly(-oxazoline)s to reveal the influence of different non-active SGs distal S. cerevisiae >6-log reductions [81] to the cationic end groups on the antimicrobial effect (Table 4B) [98]. They found that the antimicrobial activity can be controlled over several orders of magnitude, illustrating the fact that hydrophilic SGs with necessary length activate the biocidal group while nonbasic hydrophilic groups deactivate it.…”
Section: Telechelic Polymersmentioning
confidence: 99%
“…11,12 It has been shown that the addition of charged pendants to conjugated polymers has led to enhanced antibacterial activity, with both components seemingly necessary for potent acitvity. 13,14 In some instances it has been shown that the conjugated backbone allows UV activation pathways resulting in alternative killing mechanisms which in combination with the charged pendants increases activity. 12,14 Polyphenylene ethynylene (PPE) derivatives with positively charged quaternary ammonium (QA) or alkylpyridinium or negatively charged sulfonate pendants have been found to be active against both Gram-negative and Gram-positive bacteria.…”
Section: Such Interventions Include Developing New Classes Of Biocidementioning
confidence: 99%